HUBUNGAN KERJA TIM DENGAN MISSED NURSING CARE DALAM PERAWATAN PASIEN DI RUMAH SAKIT (Jurnal Perawat Indonesia, 2021)
Nurse has an important role in providing nursing care without missing. The incident of missed nursing care can cause problems that reduce the quality of patient satisfaction. This quality can be maintained by effective teamwork. The purpose of this study was to determine the relationship between teamwork and missed nursing care in patient care at the hospital. This cross-sectional study was condacted online to 93 nurses. The self-report data were collected using the MISSCARE survey questionnaire to measure the incidence of missed nursing care and nursing teamwork survey (NTS) to measure teamwork. The sampling technique used in this study is nonprobability sampling with a consecutive sampling. The data were analyzed though Spearman’s-Rho test with alpha